2022
DOI: 10.3390/polym14142905
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation by Spray Drying and Antioxidant Activity of Phenolic Compounds from Tucuma Coproduct (Astrocaryum vulgare Mart.) Almonds

Abstract: The industrial processing of fruits in the Amazon region, such as tucuma, generates a large amount of coproducts with great nutritional potential. In this work, phenolic compounds from tucuma coproduct almonds were extracted and microencapsulated by spray drying using maltodextrin as the encapsulating agent and verified its antioxidant activity. Phenolic compounds were determined by UV spectroscopy and identified by Ultraefficiency Liquid Chromatography. Antioxidant activity was measured by ABTS and DPPH assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 80 publications
2
16
0
2
Order By: Relevance
“…According to the conditions tested (4.5 mL min −1 of flow rate, 125 °C of inlet air temperature and 35 L h −1 of dry air flow rate), the experimental value of S / N was higher than the expected, with a percentage of inhibition of lipid oxidation of 87.40% ± 1.96%. Other research works already demonstrated that the total phenolic content of vegetable extracts is susceptible to temperatures as 100 °C (Ferreira et al ., 2022), 110 °C (Tran & Nguyen, 2018), 130 °C (Loan et al ., 2016) and 90–150 °C (Reblova, 2012) but despite that some yields were obtained in the respective processes. In the case of pomegranate peel polyphenols, it was reported that, in sunflower oil used in a deep‐frying potato process, they had an inhibitory effect against lipid oxidation at 180 °C and also reduced the production of acrylamide, a carcinogenic compound (Mekawi et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the conditions tested (4.5 mL min −1 of flow rate, 125 °C of inlet air temperature and 35 L h −1 of dry air flow rate), the experimental value of S / N was higher than the expected, with a percentage of inhibition of lipid oxidation of 87.40% ± 1.96%. Other research works already demonstrated that the total phenolic content of vegetable extracts is susceptible to temperatures as 100 °C (Ferreira et al ., 2022), 110 °C (Tran & Nguyen, 2018), 130 °C (Loan et al ., 2016) and 90–150 °C (Reblova, 2012) but despite that some yields were obtained in the respective processes. In the case of pomegranate peel polyphenols, it was reported that, in sunflower oil used in a deep‐frying potato process, they had an inhibitory effect against lipid oxidation at 180 °C and also reduced the production of acrylamide, a carcinogenic compound (Mekawi et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…temperature and 35 L h À1 of dry air flow rate), the experimental value of S/N was higher than the expected, with a percentage of inhibition of lipid oxidation of 87.40% AE 1.96%. Other research works already demonstrated that the total phenolic content of vegetable extracts is susceptible to temperatures as 100 °C(Ferreira et al, 2022), 110 °C(Tran & Nguyen, 2018), 130 °C(Loan et al, 2016) and 90-150 °C (…”
mentioning
confidence: 98%
“…With few modifications, the methodology proposed by Ferreira et al . (2022) and Gabriel et al . (2015) was used to perform differential scanning calorimetry (DSC) measurements of the obtained samples.…”
Section: Methodsmentioning
confidence: 96%
“…Glass transition temperature (Tg) is a vital parameter in the spray drying technique as this property is strongly International Journal of Food Science and Technology 2023 associated with the adhesion and agglomeration of the material within the drying chamber (Gabriel et al, 2015). Different authors (Gabriel et al, 2015;Ferreira et al, 2022) mentioned that material sticking during processing is likely to occur when the working temperatures exceed the material's Tg by 20 °C. Table 4 shows the Tg of CA, maltodextrin and gum Arabic and ECA.…”
Section: Dsc Of Encapsulate and Materialsmentioning
confidence: 99%
See 1 more Smart Citation